A retrospective review of operative vaginal delivery among indian patients in Hospital Tuanku Ja'afar Seremban: maternal and fetal outcomes - Ghani, Nur Fadhilah Ab (2023)
Introduction: The term operative vaginal delivery refers to a delivery in which the operator used an instrument to facilitate the delivery of the fetus. The two methods used in operative vaginal delivery are vacuum and forceps. Both instruments used are associated with risks to the maternal and neonatal. The purpose of this study is to determine the prevalence, the indications of operative vaginal delivery, and the maternal and neonatal outcomes among Indian patients who delivered via operative vaginal delivery in Hospital Tuanku Ja’afar, Seremban, Negeri Sembilan. Method: A retrospective study was conducted by reviewing 269 medical records among Indian women who delivered via operative vaginal delivery in Hospital Tuanku J’afar, Seremban from 1st January 2015 to 30th April 2021. Only singleton live birth delivery >35 weeks gestational age with normal fetus was included in the study. Statistical analysis was performed with SPSS Version 26. This study has been approved by the Research and Ethics Committee of the School of Medical Science, USM (JEPeM-USM), with assigned study protocol code USM/JEPeM/21040295, and the National Medical Research Registry (NMRR), Ministry of Health Malysia, with assigned study protocol code NMRR-21-566-59242. Results: Operative vaginal deliveries rates in this study were 4.1%. A total of 269 participants were recruited for this study, 233 (86.6%) were vacuum and 36 (15.4%) were forceps assisted deliveries. The indications for operative vaginal deliveries was similar between the two study groups and fetal distress was the most common indication for both ways of operative vaginal delivery (93.1% and 94.4%, respectively). There was no significant difference in maternal outcomes between the two-study groups. Post-partum haemorrhage and lateral vaginal wall tear did not differ significantly between vacuum and forceps delivery. There were no significant differences between vacuum and forceps-assisted delivery with regards to Apgar score <5 in 1 minute (9.4% versus 8.3%, p=0.613), Apgar score <7 in 5 minutes (6.4% versus 2.8%, p=0.409). There was no significant difference between vacuum and forceps-assisted delivery group with regards to admission to NICU or SCN, with p-value=0.347. In vacuum-assisted delivery group, 46 babies (19.7%) required intubation and in forceps-assisted delivery group 5 babies (13.9%) required intubation. In vacuum-assisted delivery group, 34 babies (14.6%) sustained cephalhematoma and in forceps-assisted delivery group 1 baby (2.8%) sustained cephalhematoma. Conclusion: Results of the present study showed vacuum was used more frequently than forceps. Both instruments are safe methods used in operative vaginal delivery in the hand of a trained operator. Enhanced training of obstetricians in instrumental delivery may aid in further reducing the prevailing caesarean section rates.